Genome-wide analysis of the CaHsp20 gene family in pepper: comprehensive sequence and expression profile analysis under heat stress - Guo, Meng; Liu, Jin-Hong; Lu, Jin-Ping; Zhai, Yu-Fei; Wang, Hu; Gong, Zhen-Hui; Wang, Shu-Bin; Lu, Ming-Hui (Frontiers in Plant Science, 2015)
The Hsp20 genes are present in all plant species and play important roles in alleviating heat stress and enhancing plant thermotolerance by preventing the irreversible aggregation of denaturing proteins. However, very little is known about the CaHsp20 gene family in pepper (Capsicum annuum L.), an important vegetable crop with character of temperate but thermosensitive. In this study, a total of 35 putative pepper Hsp20 genes (CaHsp20s) were identified and renamed on the basis of their molecular weight, and then their gene structure, genome location, gene duplication, phylogenetic relationship and interaction network were also analyzed. The expression patterns of CaHsp20 genes in four different tissues (root, stem, leaf and flower) from the thermotolerant line R9 under heat stress condition were measured using semi-quantitative RT-PCR. The transcripts of most CaHsp20 genes maintained a low level in all of the four tissues under normal temperature condition, but were highly induced by heat stress, while the expression of CaHsp16.6b, 16.7 and 23.8 were only detected in specific tissues and were not so sensitive to heat stress like other CaHsp20 genes. In addition, compared to those in thermotolerant line R9, the expression peak of most CaHsp20 genes in thermosensitive line B6 under heat stress was hysteretic, and several CaHsp20 genes (CaHsp16.4, 18.2a, 18.7, 21.2, 22.0, 25.8 and 25.9) showed higher expression levels in both line B6 and R9. These data suggest that the CaHsp20 genes may be involved in heat stress and defense responses in pepper, which provides the basis for further functional analyses of CaHsp20s in the formation of pepper acquired thermotoleance.